Paul Hymans Belgium - Marks, Sally (Haus histories, 2010)
Paul Hymans was the champion of the small states in the League of Nations Commission at the Paris Peace Conference and was rewarded by becoming the League's first president. He thereby brought about Belgium's transition from the status of sheltered child to full participation in much great-power diplomacy.